2020
DOI: 10.1017/dmp.2020.12
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Mortality From 2015 Gorkha Earthquakes of Nepal: Evidence and Future Recommendations

Abstract: Objective: The aim of this study was to explore the mortality pattern due to Gorkha earthquakes in 2015 and review the response and recovery efforts immediately following the earthquakes. Methods: Data from published reports of the Nepal Police showed over 8000 deaths. These death counts were categorized by gender, ethnicity, and age groups (interval of 5 years). The mortality rate was calculated (per 100 000 population), using the projected population as the denominator as of April 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Nepal’s health system suffers from poor coverage and quality of health services particularly at the existing ~ 5000 health facilities [ 4 , 5 ]. Nepal’s already strained health system was worsened by the damages due to the Gorkha earthquakes; and is inevitably going to be impaired by the current pandemic [ 6 ].…”
Section: Impacts Of Gorkha Earthquakes and Covid-19 Pandemic On Nepalmentioning
confidence: 99%
See 1 more Smart Citation
“…Nepal’s health system suffers from poor coverage and quality of health services particularly at the existing ~ 5000 health facilities [ 4 , 5 ]. Nepal’s already strained health system was worsened by the damages due to the Gorkha earthquakes; and is inevitably going to be impaired by the current pandemic [ 6 ].…”
Section: Impacts Of Gorkha Earthquakes and Covid-19 Pandemic On Nepalmentioning
confidence: 99%
“…COVID-19 pandemic mirrors the impact of Gorkha earthquakes, with impacts more prominent on vulnerable population living in rural and border areas that includes wage-based labourers returning from India or the stranded population desperately seeking government’s attention. Mortality associated to Gorkha earthquakes was high among vulnerable population that included children <10 years, adults >55 years, females, and from remote mountains [ 5 ]. The higher risk of infections and mortality among these specific population shows important bottlenecks in Nepal’s health system and its ability to plan and prepare for future disasters/pandemics.…”
Section: Impacts Of Gorkha Earthquakes and Covid-19 Pandemic On Nepalmentioning
confidence: 99%
“…Strengthening provincial/local health care system, resources essential for early identification, referral, isolation, and management of cases at a community level is another area which needs utmost attention (Marahatta et al, 2020). As the pandemic has already brought a wave of mortality in even the robust health systems, it is critical for Nepal to prepare and learn from the past disasters (including from these countries) for efficient preparedness and management (Adhikari et al, , 2017(Adhikari et al, , 2020 Amidst these potential constraints that Nepal can face, at least in the nearest term, Nepal should form a capacity through a team of disease specialist (trained personnel), public health specialist, laboratory personnel, and logistics management team, akin to forming a disaster management capacity/workforce . Indeed, such a workforce can remain as a reserve and 'ready to go' to the places where the outbreak of COVID-19 emerges.…”
Section: Health System Capabilitiesmentioning
confidence: 99%
“…House owners, hotel owners and community members were found to discriminate the health care workers restricting them to stay at their place. Thus, there is a need of more concerted and coordinated actions from all sides, including those who are not directly associated with the health care institutions to ensure that the actions and efforts in fighting against the COVID-19 pandemic occurs in unison (Adhikari et al, , 2017(Adhikari et al, , 2020Adhikari and Mishra, 2019;Cash and Patel, 2020;Marahatta et al, 2020)…”
Section: Health System Capabilitiesmentioning
confidence: 99%
“…The 2015 earthquakes in Nepal caused massive mortality and morbidity [ 11 ], including among the young population [ 12 ]. Prior studies have indicated that there were 8151 deaths, and mortality was higher among females, ethnic minorities, children under 10 years of age and the elderly [ 13 ]. Post-earthquake mental health outcomes among adults have been reported [ 14 , 15 ], but evidence regarding mental health impacts among youth is limited.…”
Section: Introductionmentioning
confidence: 99%